ANMERKUNGEN ZUR SEPTUAGINTA VON JES 7,14 - Oláh, Zoltán (Sacra scripta, 2013)
The Septuagint of Isa 7, 14 is one of the most discussed verses in the Bible, from Iustinus the martyr´s Dialogus cum Triphone on. Also in the modern research a high attention is dedicated on the issue of messianism in the Septuagint of Isaiah. My paper discusses only two aspects of the old Greek translation of Jes 7, 14. Firstly: Has the subject of the name giving on Immanuel any importance in this sense? Secondly: is the translation of hm'ªl.[;h' with h` parqe,noj really so meaningless, without any messianic accent, as it is supposed in few recent research?